Use of the radio frequency identification system in stock management in the automotive sector (Research, Society and Development, 2020)
The objective of this article was to evaluate the benefits of implementing radio frequency identification technology (RFID - Radio Frequency Identification) in a large company in the automotive sector, aiming at its impact on the agility and effectiveness of administrative processes, quality and Lean Manufacturing. The RFID system has the function of pointing and tracking the item in stock in order to streamline the process through automation and accessibility, allowing the visualization of what entered, left and is in stock in real time. In this way it was possible to verify if there is an increase in the efficiency of the process both in the insertion of the material in the system, as well as in facilitating the traceability of the same in the virtual stock. With these procedures, time was optimized with physical inventories to avoid problems with errors of not performing a systematic write-off of inputs in actively registered stock, but physically absent or divergent quantities in the relation of input, processes and output of metal plates and priority items in the scales and levels of significance of the ABC curve in the production of chassis for buses, trucks and agricultural wheels.